Aktivitas Penghambatan Trichoderma Spp. Formulasi Terhadap Jamur Patogen Tular Tanah Secara In Vitro = In Vitro Inhibition Activity Of Formulated Trichoderma Spp. Against Soil-Borne Pathogenic Fungi - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Hama Penyakit Tumbuhan Fak. Pertanian UGM, 2002)
Abstract: The research was aimed to evaluate the growth of formulated conidia propagules of Trichoderma koningii, T. reesei, and T. harzianum, which had been stored for 1 and 5 months and the inhibition activity against soil borne plant pathogenic fungi Rigidopous lignosus, Ganoderma sp., Fusarium sp., and Sclerotium rolfsii. The isolate were formulated in the forms of alginate bead, alginate peat bead, and peat-lime powder. The results indicated that Trichoderma whose formula stored at room temperature showed higher inhibition activity than that stored at 4 'C. After 5 months in the storage, T. reesei in both bead and powder formula performed higher growth inhibition activity against soil borne pathogens than the other isolates tested. It was noted that all isolates performed temporary decreased growth inhibition activity against soil borne pathogens.